PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN SPIRITUALITAS KERJA SEBAGAI VARIABEL INTERVENING PADA FIGHTER CONVECTION - Dimas Cokro Buwono; Ali Mauludi AC (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
In the increasingly competitive era, Fighter must not only focus on expanding its consumer base but also pay attention to its employees' performance. Factors influencing employee performance include the work environment, compensation, motivation, and work spirituality. The goal of this research is to determine the direct and indirect impact of the work environment, compensation, and motivation on employee performance, with work spirituality as an intervening variable. This study employs a quantitative approach with primary data sources and utilizes multiple linear regression analysis. Data collection involves a survey method with a questionnaire technique. The population consists of all Fighter Convection employees, with a sample size of 47 selected through saturation sampling. The findings indicate that the work environment does not significantly influence work spirituality or employee performance. Similarly, compensation and motivation do not have a significant impact on work spirituality or employee performance. However, work spirituality significantly and positively influences employee performance. Furthermore, work spirituality does not mediate the relationship between the work environment, compensation, motivation, and employee performance at Fighter Convection.